2020
DOI: 10.1155/2020/1291342
|View full text |Cite
|
Sign up to set email alerts
|

Research on Decision-Making Behavior of Discretionary Lane-Changing Based on Cumulative Prospect Theory

Abstract: In this paper, the decision-making model of discretionary lane-changing is established using cumulative prospect theory (CPT). Through analyzing the vehicles’ dynamic running states, safety spacing calculating approaches for discretionary lane-changing and lane-keeping have been put forward firstly. Then, based on CPT, a lane-changing decision model with accelerating space as its utility is proposed by estimating the difference between actual spacings and the safety spacings for discretionary lane-changing as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For level 2, these main factors were further distributed into fourteen sub-factors and, for level 3, these were further distributed into eight sub-factors. Many researchers considered these specified factors significant in related studies, such as lanechange crashes [42,52], lane-change risks [53], lane-changing simulation [26], discretionary lane-changing [27,54] and road-safety evaluation [44].…”
Section: Lane-change Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For level 2, these main factors were further distributed into fourteen sub-factors and, for level 3, these were further distributed into eight sub-factors. Many researchers considered these specified factors significant in related studies, such as lanechange crashes [42,52], lane-change risks [53], lane-changing simulation [26], discretionary lane-changing [27,54] and road-safety evaluation [44].…”
Section: Lane-change Modelmentioning
confidence: 99%
“…Studying the unpredictability of the lane-changing period, a previous study [27] investigates that the least possible safety layout alters with the dynamic lane-changing period and explains how the accelerating space of the actual vehicle alters with the nearby vehicles' running positions. On this basis, a decision-making model of discretionary lane-changing based on dynamic reference spots was created using cumulative prospect theory (CPT).…”
Section: Introductionmentioning
confidence: 99%
“…In simple words, at the value of θ = 5, the DMs become less sensitive toward losses (as compared to θ = 1), and thus, they tend to choose the desired lanes with the maximum number of lane changes to decrease their delay. Furthermore, the higher value of θ means that the driver gets promoted to change the lanes [ 50 ] and decide the lane by evaluating the criteria (such as lane with the minimum number of vehicles in the queue or with less proportion of heavy vehicles) in the front space (i.e., flare area in the diverging zone of toll plaza). It illustrates the risk-seeking behavior of the DMs when presented with the gain.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method was flexible and provided better results than the artificial intelligence-based methods. Long et al [ 50 ] used the cumulative prospect theory for the study of lane-changing behavior. They concluded that the cumulative prospect theory predicts lane changes better due to the presence of risk aversion factor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, discretionary lanechanging has a certain degree of autonomy and non-necessity. Moreover, sometimes it will be affected by objective conditions and subjective factors to make the decision of giving up lane-changing [18]. As shown in Figure 1, in the discretionary lane-changing scene of one-way double lane, there are FV(Front vehicle) in front of the target lane, PV(Preceding vehicle) in front of the current lane, RV(Rear vehicle) in the rear of the target lane and LV(Lane-changing vehicle) in the current lane, which run along the lane centerline respectively.…”
Section: Analysis Of Lane-changing Behaviormentioning
confidence: 99%